Pengembangan Modul Etnomatematika Berbasis Budaya Dayak dalam Pembelajaran Matematika dengan Pendekatan Joyfull Learning - Niken Eka Priyani (Jurnal Didaktika Pendidikan Dasar, 2021)
The conditions of the Covid-19 pandemic caused learning to change to once a week, limited teaching materials at SDN 29 Idai, and a decrease in the values of preserving Dayak culture in Idai village. Through the integration of the concepts of mathematics and culture, this study aims to develop an ethnomathematics module based on the Dayak culture in mathematics learning with a joyful learning approach. This research is a research development or Research and Development (R & D) with a research method using the Hanafin & Peck development model which focuses on solving problems of quality constraints and development complexity which consists of three stages, namely; 1) needs assessment; 2) the design stage, and 3) development and evaluation. The data collection technique used observation, interview, and ethnomathematics module validation sheets which were filled in by two reviewers, while module trials were conducted in grade 4 SDN 29 Idai. The results showed that the ethnomathematics module based on the Dayak culture with a joyful learning approach got good results so that it could be used to teach math concepts to grade 4 students at SDN 29 Idai.